JPMI - A JOURNEY OF TWENTY FIVE YEARS: IT IS JUST THE BEGINNING... - Javaid, Arshad (Journal of Postgraduate Medical Institute, 2011)
Postgraduate Medical Institute (PGMI) was established in August 1984. Sadly both the founders, Dean Professor Jamil Ahmed and Governor General Fazal Haq who must be credited with the vision and its implementation of first PGMI in the province, are not amongst us today. However, their vision of creating a PGMI as centre of excellence for postgraduate training in the province of Khyber Pakhtunkhwa has been realized. JPMI and its progress over the last 25 years is a living testimony to that.